Glaukome im stationären Leistungsgeschehen in Deutschland in 2015 - Hahn, Ursula; Kretz, Florian Tobias Alwin; Koch, Jörg-Michael (Der Ophthalmologe, 2019)
AimAnalysis of structural characteristics of inpatient treatment of glaucoma in clinical units run by affiliated physicians and those run by hospital physicians in Germany are described. The frequency and distribution of glaucoma diagnoses as the main and secondary diagnosis at different departments and glaucoma diagnoses, number of cases, surgeries and procedures and patient characteristics of the four glaucoma-specific diagnosis-related groups (DRG) are presented.MethodSecondary data analysis using the G‑DRG browser from 2015/2016 provided by the German Institute for Remuneration Systems in Hospitals.ResultsIn 30% of the 156,524 cases glaucoma was classified as the main diagnosis, in 24% as secondary diagnosis in ophthalmological departments and 46% as secondary diagnosis in other departments. Primary open angle glaucoma was reported most frequently (40%), whilst non-ophthalmological departments mainly coded as “other” or “unspecified types of glaucoma”. Glaucoma was coded in 20 DRGs as the main diagnosis and in all ophthalmic DRGs as secondary diagnosis. The number of cases and procedures differed among the four glaucoma-specific DRGs (C06Z, C07A, C07B, C64Z), the diagnostic spectrum, however, was similar. Patients were mainly women, older and with few comorbidities or complications. The C64Z was mainly characterized by cases with “suspected glaucoma” and only conservative procedures. Only 6% of the glaucoma patients were treated in clinical units run by affiliated physicians. In contrast to units run by hospital physicians surgical DRGs and operations prevailed but the diagnostic spectrum and patient characteristics were not different.Discussion and conclusionWith 20% of the main diagnoses, glaucoma was highly relevant for inpatient ophthalmological care. Glaucoma as a secondary diagnosis was also common in other medical specialties, though no diagnostic differentiation was made here. Patients with glaucoma are mainly treated in clinical units run by hospital physicians. Nevertheless, patients of affiliated physicians showed the same characteristics.
Published: 06 July 2018
Gesehen am 30.09.2019